Analisis Penerapan Good Corporate Governance Dalam Upaya Melindungi Investor Di Pasar Modal - Nur Hidayah, Reza (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This study aims to find out how the implementation of Good Corporate Governance in protecting investors in the capital market. According to Article 1 point 5 of Law No. 8 of 1995 concerning Capital Markets, activities in the capital market involve high risks, so trading in securities in the form of securities is prohibited. An alternative to reduce this high risk is to implement GCG. The methodology used is descriptive qualitative, looking for data sources from various publications and previous studies, which are then analyzed. According to the findings of this study, Good Corporate Governance (GCG) is now widely recognized and used in all countries thanks to international organizations. Transparency, Accountability, Responsibility, Independence and Fairness (TARIF) are the guiding principles of Good Corporate Governance (GCG). Good Corporate Governance (GCG) seeks to protect the rights of shareholders in the capital market who are obliged to obtain accurate and timely information about issuers or companies and the interests of shareholders (securities). This could include ensuring that all shareholders, especially minorities and foreign investors, receive fair treatment, as well as disclosing pertinent information and prohibiting the distribution of shares to private individuals and insider trading.